2021
DOI: 10.3390/en14123379
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Dynamic Rock Scour Protection in Morphodynamic Environments for Offshore Wind Jackets

Abstract: Bottom-fixed offshore wind turbines are generally built on continental-shelf sections that are morphodynamically active due to their shallow depths and severe wave and current conditions. Such sites are commonly protected against scour to prevent the loss of structural stability. Scour protection can be designed using static or dynamic solutions. Designing dynamic protection requires experimental validation, especially for singular or unconventional structures. This article presents an experimental method for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…From the falling apron point of view, a low dependency of scour protection on hydrodynamic load history was found by the authors. In addition, the maximum deformation of the scour protection was found to be greatly affected by the arrival order of storms [105]. Another form of hard scour protection (shown in Figure 18b) with four layers for four-pile jacket foundations was proposed in [106] and found by tests to be effective in preventing scouring.…”
Section: Jacket Foundationmentioning
confidence: 99%
See 1 more Smart Citation
“…From the falling apron point of view, a low dependency of scour protection on hydrodynamic load history was found by the authors. In addition, the maximum deformation of the scour protection was found to be greatly affected by the arrival order of storms [105]. Another form of hard scour protection (shown in Figure 18b) with four layers for four-pile jacket foundations was proposed in [106] and found by tests to be effective in preventing scouring.…”
Section: Jacket Foundationmentioning
confidence: 99%
“…When compared with monopiles, only a handful of studies focused on scour protections for jacket foundations. Sarmiento et al [105] mentioned that a kind of rock protection (shown in Figure 18a) has been applied on at least one of the foundations of the wind farm East Anglia ONE (UK). The authors analyzed the falling apron effect and the stability of this rock scour protection for a three-pile jacket foundation.…”
Section: Jacket Foundationmentioning
confidence: 99%
“…Physical experiments allow to properly reproduce the interaction between flow, structure and soil, therefore the main objective of the physical experiments is the final estimation/validation of the equilibrium scour depth along the pile clusters, as well as the potential assessment of the global scour around the foundation. The experimental methodology was developed at IHCantabria facilities (CCOB, equivalent to the basin tests described in [15]). Considering the main characteristics of the basin (CCOB) and the size of the platforms, the scale of the test can vary from 1/35 to 1/45.…”
Section: Step Iii: Physical Experimentsmentioning
confidence: 99%